Cytokines and Chemokines in HBV Infection - Zhong, Shihong; Zhang, Tianling; Tang, Libo; Li, Yongyin (Frontiers in Molecular Biosciences, 2021)
Chronic hepatitis B virus (HBV) infection remains a leading cause of hepatic inflammation and damage. The pathogenesis of chronic hepatitis B (CHB) infection is predominantly mediated by persistent intrahepatic immunopathology. With the characterization of unique anatomical and immunological structure, the liver is also deemed an immunological organ, which gives rise to massive cytokines and chemokines under pathogenesis conditions, having significant implications for the progression of HBV infection. The intrahepatic innate immune system is responsible for the formidable source of cytokines and chemokines, with the latter also derived from hepatic parenchymal cells. In addition, systemic cytokines and chemokines are disturbed along with the disease course. Since HBV is a stealth virus, persistent exposure to HBV-related antigens confers to immune exhaustion, whereby regulatory cells are recruited by intrahepatic chemokines and cytokines, including interleukin-10 and transforming growth factor β, are involved in such series of causal events. Although the considerable value of two types of available approved treatment, interferons and nucleos(t)ide analogues, effectively suppress HBV replication, neither of them is sufficient for optimal restoration of the immunological attrition state to win the battle of the functional or virological cure of CHB infection. Notably, cytokines and chemokines play a crucial role in regulating the immune response. They exert effects by directly acting on HBV or indirectly manipulating target immune cells. As such, specific cytokines and chemokines, with a potential possibility to serve as novel immunological interventions, combined with those that target the virus itself, seem to be promising prospects in curative CHB infection. Here, we systematically review the recent literature that elucidates cytokine and chemokine-mediated pathogenesis and immune exhaustion of HBV infection and their dynamics triggered by current mainstream anti-HBV therapy. The predictive value of disease progression or control and the immunotherapies target of specific major cytokines and chemokines in CHB infection will also be delineated.